2016
DOI: 10.4103/0253-7613.182881
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study to evaluate the antiosteoporotic effect of Panchatikta Ghrita in a steroid-induced osteoporosis rat model

Abstract: Objective:The study was conducted to develop the glucocorticoid-induced osteoporosis (GIO) model in Sprague-Dawley weanling rats using different doses of methylprednisolone (MP) and evaluate the antiosteoporotic effect of a classical ayurvedic formulation, Panchatikta Ghrita (PG), in this model.Materials and Methods:Institutional Animal Ethics Committee approval was obtained. Development of model was done by subcutaneous injection of 2 doses of MP (14 and 28 mg/kg/week) for 4 weeks in 21-day old weanlings. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Panchatikta Ghrita (PG), a classical ayurvedic formulation has plant ingredients that, as per Ayurveda, have properties of tikta rasa which maintains the dhatvagni in normal state which in turn keeps all the dhatus in the body in equilibrium. As asthi dhatu (related to bone tissue) becomes stable, bone degeneration decreases [11] , [17] . Thus, this formulation, based on the osteoprotective properties of its plant ingredients, protects against bone degeneration and loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Panchatikta Ghrita (PG), a classical ayurvedic formulation has plant ingredients that, as per Ayurveda, have properties of tikta rasa which maintains the dhatvagni in normal state which in turn keeps all the dhatus in the body in equilibrium. As asthi dhatu (related to bone tissue) becomes stable, bone degeneration decreases [11] , [17] . Thus, this formulation, based on the osteoprotective properties of its plant ingredients, protects against bone degeneration and loss.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we had studied the protective effect of the same formulation against an experimental model of glucocorticoid induced osteoporosis [11] . The results demonstrated that Panchtikta ghrita protected against worsening of bone degeneration in this model of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Panchatikta Ghrita (PG) stated its anti-osteoporotic properties in rats. PG administration in osteoporosis induced rats demonstrated better serum calcium and inorganic phosphate levels, reduced urinary calcium and phosphate levels, decreased osteoclasts, and increased bone hardness compared to the diseased group [ 128 ]. Later another study be the same authors show promising effects of PG in protecting against postmenopausal osteoporosis [ 129 ].…”
Section: Review Of Modern Literature On Ghee In Context Of the 15 Ben...mentioning
confidence: 99%
“…Завдяки значному прогресу біології в останні роки існує мож-ливість аналізувати дію багатьох чинників, котрі впливають на метаболізм кісткової тканини, як in vivo, так і in vitro, що призвело до більш активного використання експери-ментального моделювання на тваринах [1][2][3][4][5][6]. Проте існуючі сучасні методи оцінки стану й метаболізму кісткової тканини є інвазивними (гістоморфометричне дослідження, визначен-ня біохімічних маркерів кісткового ремоде-лювання в сироватці крові тощо) і неінвазив-ними (комп'ютерна томографія, двофотонна рентгенівська денситометрія -ДРА), що може обмежувати оцінку результатів дослідження в динаміці експерименту [1,7,8].…”
Section: вступunclassified